Perancangan Sistem Pelaporan Keluhan Pelanggan Berbasis Website Menggunakan Metode Waterfall - Adnan Buyung Nasution; Lubis, Bayu Fadhli Erlangga; Nurul Amanda Khairani Lubis; Friska Andriani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The development of information technology has created devices that can help complete work very easily. Nowadays, many agencies and organizations use technology to complete tasks and work, one of which is keeping records using technology in providing services to customers who want to make complaints. Tirtanadi Medan Regional Drinking Water Company (PDAM) is a regional company in the province of North Sumatra. PDAM's waste water marketing branch itself was established in 2019. This is in line with the issuance of Medan Mayor Regulation No. 29 of 2019. PDAM Tirtanadi's Waste Water Marketing Branch receives customer complaints every day. PDAM Tirtanadi's Waste Water Marketing Branch still operates the system. manual, namely recording all customer complaints using a book and storing the files in a cupboard. This makes it difficult for contact parties and technicians to find data which continues to increase every time. The solution to the problems that occur at PDAM Tirtanadi Waste Water Marketing Branch is building a Website-Based Customer Complaint Reporting System at PDAM Tirtanadi Waste Water Marketing Branch which is part of the objectives of this research. This system was developed using the waterfall method. The results of this research created a Website-Based Customer Complaint Reporting System which is expected to make it easier for people to find customer complaint data and help technicians to speed up the process of repairing problems that occur to PDAM Tirtanadi Waste Water Marketing Branch customers.